Production of antioxidant compounds from tissue culture of Artemisia annua - AMALIA INDAH PRIHANTINI; AGUS SUKITO; SANRO TACHIBANA (Smujo International, 2018)
Prihantini AI, Sukito A, Tachibana S. 2018. Production of antioxidant compound from tissue culture of Artemisia annua. Nusantara Bioscience 10: 251-255. Phenolic compounds have attracted much attention because of their role in some oxidative diseases. Therefore, the study aimed to investigate the production of antioxidant compound from tissue culture of A. annua. The callus were developed on solid MS medium treated with four combination of plant growth regulators: NAA 0.5 mg/L + BA 0.5 mg/L; NAA 0.5 mg/L + kinetin 0.5 mg/L; 2,4-D 0.5 mg/L + BA 0.5 mg/L; and 2,4-D 0.5 mg/L+ kinetin 0.5 mg/L. The callus extracts were evaluated their antioxidant activity and were analyzed the content of phenolic content. Furthermore, detection and quantification of phenolic compound were investigated. Combination of NAA 0.5 mg/L + BA 0.5 mg/L showed the highest DPPH radical scavenging activity and total phenolic content. GCMS analysis also revealed that the combination also showed the highest content of caffeic acid, a phenolic compound known as an antioxidant agent. Furthermore, the callus extract treated with NAA 0.5 mg/L + BA 0.5 mg/L increased both the antioxidant activity and caffeic acid content compared with A. annua leaf extract. In conclusion, plant tissue culture enhanced pharmaceutical properties of A. annua. Moreover, the study suggested that the treated callus extract of A. annua is potential to be further developed for production of antioxidant compound.